Classification of Poisonous Ornamental Plants Using CNN and ResNet Methods - Ahmad Halimi; Eka Herliana Agustini; Nur Diyana Kholidah (Khatulistiwa : Journal of Artificial Intelligence, 2025)
This research, titled